Emotional Intelligence as an Evolutive Factor on Adult With ADHD. Issue 10 (August 2020) - Quintero, Javier; Vera, Rosa; Morales, Isabel; Zuluaga, Pilar; Fernández, Alberto
Objective: ADHD adults exhibit deficits in emotion recognition, regulation, and expression. Emotional intelligence (EI) correlates with better life performance and is considered a skill that can be learned and developed. The aim of this study was to assess EI development as ability in ADHD adults, considering the effect of comorbid psychiatric disorders and previous diagnosis of ADHD.Method: Participants ( n = 116) were distributed in four groups attending to current comorbidities and previous ADHD diagnosis, and administered the Mayer–Salovey–Caruso Emotional Intelligence Test version 2.0 to assess their EI level.Results: ADHD adults with comorbidity with no previous diagnosis had lower EI development than healthy controls and the rest of ADHD groups. In addition, ADHD severity in childhood or in adulthood did not influence the current EI level.Conclusion: EI development as a therapeutic approach could be of use in ADHD patients with comorbidities.